The Ranking Argument - Challenging Favourable Comparative Rhetoric about Swiss Animal Welfare Law - Christian Rodriguez Perez; Nico Dario Müller; Kirsten Persson; David Martin Shaw (Journal of Animal Law, Ethics and One Health)
This article captures and critiques a recurring and prominent political argument against animal welfare improvements in Switzerland which we term the “ranking argument”. This states that Swiss animal welfare law ranks among the strictest in the world, therefore no improvements are called for. This argument was advanced three times by Swiss government authorities in 2022 alone, but also in a case dating back to 1984, to advise the electorate on popular initiatives aiming at animal welfare improvements. We argue that, while the argument commits a fallacy of relative privation and is ethically dubious, it can be deployed to great effect by agents opposed to norm change in animal welfare regulation. We conclude with some thoughts on how the ranking argument can and should be challenged in public discourse.